IMPLEMENTATION OF FLUTTER FRAMEWORK IN DEVELOPING A MOBILE EMPLOYEE ATTENDANCE APPLICATION FOR BLAHKIUH VILLAGE GOVERNMENT - Putu Adi Guna Permana; Komang Drei Bayu Anggara; Komang Yuli Santika (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
In recent years, mobile applications have become vital tools for improving the efficiency of administrative tasks, particularly within government organizations. This research focused on creating a mobile attendance system tailored for Blahkiuh Village employees, leveraging the Flutter framework. This framework was selected due to its ability to produce fast, reliable, and cross-platform apps that work seamlessly on both Android and iOS devices.The app was designed to address the inefficiencies of the previous manual attendance process, which often led to inaccuracies and delays. Key features of the development process included crafting a user-friendly interface, integrating a secure database for precise data storage, and conducting rigorous testing to ensure optimal functionality.Initial implementation of the system has shown notable improvements, such as reducing errors in attendance records, streamlining data entry processes, and providing real-time reporting capabilities. This innovation not only simplifies attendance tracking but also serves as a digital solution that can be expanded to other administrative functions in Blahkiuh Village.